80.3k views
2 votes
Please help me with this please.

Please help me with this please.-example-1

1 Answer

3 votes

Answer:

f(-2) = -1

f(0) = -5

f(4) = -1

Explanation:

The number inside of f( ) is telling you which equation to use to get the answer.

Example:

f(-2) since -2 is less than 0 you would use (x^2) - 5. So, ((-2)^2) - 5 = 4-5 = -1

f(0) since 0 is less than or equal to 0 you would use (x^2) - 5 again. So, ((0)^2) - 5 = 0-5 = -5

f(4) since 4 is grater than 3 you would use (2^(x-1)) - 9. So, (2^(4-1)) - 9 = -1

The Graph, try to make it as straight as possible

Please help me with this please.-example-1
User Zach Folwick
by
7.5k points